Identification and characterisation of the P2Y14 purine receptor in the porcine coronary artery - Abbas, Z.S.B (2017)
Introduction: The P2Y14 receptor, with its unique pharmacologic profile, is the only member of its P2Y family that is activated by UDP-sugar nucleotides as well as MRS2690, the synthetic analogue of UDP-glucose. Its role in the immune and inflammatory systems is well documented; however its role in the cardiovascular system and, particularly, the vasculature is beginning to emerge. Aims and Objectives: The aim was to provide evidence for the expression and the role of the P2Y¬14 receptor in porcine coronary arteries. The objectives of the study were to characterize the P2Y14 receptor response profile in the presence of a P2Y14 receptor antagonist, PPTN, in the porcine coronary artery using organ bath pharmacology. The effects of non-selective P2 receptor antagonists, suramin and PPADS and the P2Y¬6 receptor antagonist MRS2578, on responses to UDP-glucose and MRS2690 were investigated. P2Y14 receptor protein expression and receptor localization was explored using Western blot and immunohistochemistry. P2Y14 receptor coupling to the inhibition of adenylyl cyclase/cAMP activity, using a vasodilator-stimulated phosphoprotein phosphorylation (VASP-P) bead assay, in porcine coronary arteries was determined. Human isolated red blood cells (RBCs) and platelets as sources of UDP-glucose were investigated. Hypoxia-induced release of UDP-glucose from porcine coronary arteries was also investigated. The function of the P2Y14 receptor as an anti/pro-inflammatory stimulus in porcine coronary arteries was also explored. Results: UDP-glucose, UDP-N-acetylglucosamine and UDP-glucuronic acid elicited concentration-dependent contractions in the porcine coronary artery; MRS2690-induced contractions were 10-fold more potent than those of the UDP-sugars. The contractile responses to MRS2690, but not UDP-glucose, were significantly inhibited by PPTN (3 µM) (in presence of U46619 and forskolin to precontract and raise cAMP, respectively). The contractile responses to UDP-glucose, but not MRS2690, were altered (either inhibited or potentiated) in the presence of suramin and PPADS. MRS2578, a P2Y6 receptor antagonist, did not change the contractile responses to UDP-glucose or MRS2690 in U46619 preconstricted coronary arteries. MRS2578 did not change the contractile responses to MRS2690, but did to UDP-glucose (in the presence of forskolin plus U46619). Immunoblotting showed that the P2Y14 receptor protein exists in two isoforms, sized 41 kDa and 61 kDa in porcine coronary arteries. Immunohistochemistry revealed localization of P2Y14 receptors in the vascular smooth muscle cells and endothelium of porcine coronary arteries. UDP-glucose and MRS2690 significantly decreased VASP-P in coronary arteries, an effect which was partially reversed in the presence of PPTN. Red blood cells induced contractions in preconstricted porcine coronary arteries; the response remained unchanged in the presence of PPTN. Platelets induced relaxations and contractions in the absence and presence of L-NAME (inhibitor of nitric oxide synthase), respectively, in porcine coronary arteries; the response remained unchanged in the presence of PPTN. PPTN does not change hypoxia induced relaxation in preconstricted coronary arteries. UDP-glucose and MRS2690 had no significant effect on the release of cytokines/chemokines from segments of coronary arteries. Conclusion: The action of UDP-sugars and MRS2690, P2Y14 receptor agonists, as inducers of contraction is consistent with an involvement of functional P2Y¬14 receptors in porcine coronary arteries. Inhibition by PPTN, a selective P2Y14 receptor antagonist, of contractile responses to a selective P2Y14 receptor agonist, MRS2690, further provides evidence of P2Y14 receptors in porcine coronary arteries. Release of purine and pyrimidine nucleotides is known to be exaggerated in pathophysiological conditions, such as shear stress, endothelial cell damage and hypoxia. This may elicit chronic activation of P2 receptors including P2Y14 receptors, consequently causing increased vasoconstriction of porcine coronary arteries. The patho/physiological sources and stimuli for local UDP/UDP-glucose release remain to be determined since PPTN did not block responses to RBCs, platelets and hypoxia under the conditions of the present study. The P2Y14 receptor may be a novel target to control abnormal vascular contraction under pathophysiological conditions.